Philosophy, Ethics, and Humanities in Medicine - Das, Devaleena; Reznicek, Mathew L.; Creechan, Louise; Romanis, Elizabeth Chloe; Theixos, Heleana; Langland, Elizabeth; FitzGerald, Kevin T.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
The Journal of Philosophy, Ethics, and Humanities in Medicine is positioned at the intersection of the humanities, social sciences, and medicine. We welcome submissions from scholars and practitioners that build interdisciplinary bridges and re-envision contributions across these disciplines. We seek to engage a more comprehensive understanding of health and wellness that purposefully aligns the wants and needs of patients and practitioners, and attends to the individual human condition and public health in ways that modern medicine has at times neglected. We invite approaches that: recognize the dual nature of medicine as both an art and a science; empower patients and caregivers; reduce health-worker burnout; engage fully with humanities and social science perspectives$1 (Band their values$1 (Bto inform medical education and practice; re-envision the integration of humanities and emerging technology in these settings.s
Keywords: Medicine$1 (BPhilosophy.s; Bioethics; Philosophy of Medicine; Bioethics